2010
DOI: 10.1074/jbc.m109.029165
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Calcium-sensing Receptor in Human Taste Perception

Abstract: By human sensory analyses, we found that various extracellular calcium-sensing receptor (CaSR) agonists enhance sweet, salty, and umami tastes, although they have no taste themselves. These characteristics are known as "kokumi taste" and often appear in traditional Japanese cuisine. Although GSH is a typical kokumi taste substance (taste enhancer), its mode of action is poorly understood. Here, we demonstrate how the kokumi taste is enhanced by the CaSR, a close relative of the class C G-protein-coupled recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
294
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(310 citation statements)
references
References 32 publications
13
294
2
1
Order By: Relevance
“…A taste receptor sensitive to calcium (Tas1r3) has been identified in mice, 116 and it is possible that the same receptor acts in humans. 117,118 In this regard, it has been suggested that another receptor, CASR, mediates kokumi taste, 117 an orosensory quality recognized in Japan but unknown in the West. Although people differ in the perception of calcium solutions, 119 there are no genetic studies to indicate whether this trait is heritable and which genes (including the genes coding the subunits of the receptor) might be involved.…”
Section: Calcium As a Basic Tastementioning
confidence: 99%
“…A taste receptor sensitive to calcium (Tas1r3) has been identified in mice, 116 and it is possible that the same receptor acts in humans. 117,118 In this regard, it has been suggested that another receptor, CASR, mediates kokumi taste, 117 an orosensory quality recognized in Japan but unknown in the West. Although people differ in the perception of calcium solutions, 119 there are no genetic studies to indicate whether this trait is heritable and which genes (including the genes coding the subunits of the receptor) might be involved.…”
Section: Calcium As a Basic Tastementioning
confidence: 99%
“…Since "tamari" from miso fermented with GGT had a stronger "kokumi" taste than without GGT, it was supposed that more γ-glutamyl compounds were formed in miso fermented by the addition of GGT, and this was confirmed. According to Ohsu et al (2010), the intensity of the enhancement of "kokumi" by γ-Glu-Val and γ-Glu-Val-Gly were 0.61 times and 12.8 times relative to glutathione, respectively. The concentrations of reduced and oxidized glutathione, γ-Glu-Val, and γ-Glu-Val-Gly in "tamari" obtained after 6 months of fermentation with and without the addition of B. subtilis GGT were measured by CE-TOF-MS. As shown in Table 1, neither reduced nor oxidized glutathione was found.…”
Section: Comparison Of the Taste Of Misomentioning
confidence: 99%
“…It was reported that some γ-glutamyl compounds, such as GSH, are "kokumi" substances (Dunkel, Koester, & Hofmann, 2007;Toelstede, Dunkel, & Hofmann, 2009;). Ohsu et al (2010) compared the enhancement of "kokumi" by various γ-glutamyl compounds and found that γ-Glu-Val-Gly is the strongest "kokumi" substance. Since GGT can also catalyze the transpeptidation reaction, some γ-glutamyl compounds might be formed from glutamine as a donor, and amino acids and peptides as acceptors when B. subtilis GGT is added to "moromi".…”
Section: Introductionmentioning
confidence: 99%
“…On the bases of our studies, a novel kokumi peptide, g-L-glutamyl-Lvalylglicine (g-Glu-Val-Gly, Fig. 21), was found out by using modern biological technique (Ohsu et al 2010). They succeeded in the cloning of sensory receptor of GSH and determined several compounds which combined to the receptor.…”
Section: Summary and Future Perspectivementioning
confidence: 99%